2009
DOI: 10.1016/j.otohns.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Response to Fungus is not Universally Associated with Rhinosinusitis

Abstract: In contrast to previously reported data, IL-5 responses to Alternaria extract were not predictive of CRS presence. Our results in patients from Utah and Texas significantly differ from previously published findings in predominantly Midwestern patients. The immunologic response to fungal extracts appears to be heterogenous and may differ based on geography, allergy status, and/or other as-yet unknown factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
0
19
0
3
Order By: Relevance
“…Part of the controversy relating to the fact that fungus is ubiquitous has been isolated in both healthy and diseased subjects . Although there has been previous evidence of disturbance in the innate and adaptive immunity associated with fungi, this has been contradicted by later studies by Orlandi et al The systematic review also has found no routine role for the use of antifungal medication in the management of CRS . A recent review article has disputed the hypothesis that fungi are the underlying causative factor for all CRS patients .…”
Section: Discussionmentioning
confidence: 99%
“…Part of the controversy relating to the fact that fungus is ubiquitous has been isolated in both healthy and diseased subjects . Although there has been previous evidence of disturbance in the innate and adaptive immunity associated with fungi, this has been contradicted by later studies by Orlandi et al The systematic review also has found no routine role for the use of antifungal medication in the management of CRS . A recent review article has disputed the hypothesis that fungi are the underlying causative factor for all CRS patients .…”
Section: Discussionmentioning
confidence: 99%
“…This response was independent of IgE sensitivity to fungi. Orlandi et al, 369 however, replicated the methods of Shin et al 368 and had opposing results. They found that IL-5 levels correlated strongly with fungal-specific IgE, but did not correlate with fungal-specific IgG as described by Shin et al 368 In a study performed by Pant et al, 370 IgG1 and IgG3 isotypes to fungi were identified in CRS patients with eosinophilic mucin.…”
Section: S55mentioning
confidence: 98%
“…2, 3). Eosinophilic mucin is now the preferred term instead of allergic mucin since there is debate regarding whether the etiology of this mucinous material, as well as allergic FRS, is allergic at all [1,2,17,18,[20][21][22][23][24][25][26][27][28][29]. Fungal hyphae are occasionally seen on H and E stain but are best highlighted by histochemical stains such as silver or periodic acid Schiff (PAS) (Fig.…”
Section: Allergic Fungal Rhinosinusitismentioning
confidence: 99%